Information at Play: The Role of Information Behaviour and Meaning-Making - Adams, Suellen S. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper relates to the conference in the area of user studies. It examines the similarities of information behaviour and meaning making in 4 studies of adult play environments. It will also make a case for the importance of studying information behaviour and meaning-making in play environments. One of these studies is now complete, the other three are ongoing, though two of these are nearly complete. Cette communication porte sur l'étude des utilisateurs et examine les similitudes entre le comportement informationnel et la formulation de sens dans quatre études sur les environnements de jeu pour adultes. Elle justifie par ailleurs l'importance d'étudier les comportements informationnels et la formulation de sens en environnement de jeu. Une de ces études est déjà complétée, les autres sont toujours en cours dont deux qui sont quasi terminées.